Analisis Kapasitas Penampang Drainase Jalan Perkotaan Akibat Peluapan Debit Banjir Maksimum (Studi Kasus Pada Jalan Jhoni Anwar Kota Padang): Analysis Of Urban Road Drainage Capacity Due To Maximum Flood Discharge Overflowing (Case Study on Jhoni Anwar Street, Padang City) - Sicilia Afriyani; Haris Haris; Iswahyudi Iswahyudi (Media Ilmiah Teknik Sipil, 2023)
The problem of flooding or inundation can arise from several factors, one of which is the incapacity of the existing drainage system to accommodate the increased volume of water flowing into it. For example, the drainage system on Jhoni Anwar Street in Padang City has become a frequent cause of flooding. This street should ideally be flood-free, especially as it serves as a major connecting road in Padang City. Therefore, the author intends to conduct research on the drainage system's capacity on this street. The data analysis required for this study includes hydrological analysis, including rainfall data, average rainfall, and flood discharge. Additionally, hydraulic analysis is also necessary, such as analyzing the existing channels, backwater analysis, planning the dimensions of the drainage system, and determining the flood points for each channel. It is known that the drainage system on Jhoni Anwar Street can only accommodate a water discharge of 0.24 m3/second, while the peak discharge during a 5-year flood period reaches 3.11 m3/second. Therefore, new dimensions for the drainage system are needed. The planned dimensions include a wet cross-sectional height of 140 cm or 1.40 m, a total cross-sectional height (h) of 160 cm or 1.60 m, and a channel width (b) of 1.42 cm or 1.42 m. With these dimensions, the channel will be able to accommodate a water discharge of 3.36 m3/second, in accordance with the criteria for peak flood discharge